Environmental DNA: What's behind the term? Clarifying the terminology and recommendations for its future use in biomonitoring - Pawlowski, Jan; Apothéloz‐Perret‐Gentil, Laure; Altermatt, Florian (Molecular ecology, 2020)
The last decade brought a spectacular development of so‐called environmental (e)DNA studies. In general, “environmental DNA” is defined as DNA isolated from environmental samples, in contrast to genomic DNA that is extracted directly from specimens. However, the variety of different sources of eDNA and the range of taxonomic groups that are targeted by eDNA studies is large, which has led to some discussion about the breadth of the eDNA concept. In particular, there is a recent trend to restrict the use of the term “eDNA” to the DNA of macro‐organisms, which are not physically present in environmental samples. In this paper, we argue that such a distinction may not be ideal, because the eDNA signal can come from organisms across the whole tree of life. Consequently, we advocate that the term “eDNA” should be used in its generic sense, as originally defined, encompassing the DNA of all organisms present in environmental samples, including microbial, meiofaunal and macrobial taxa. We first suggest specifying the environmental origin of the DNA sample, such as water eDNA, sediment eDNA or soil eDNA. A second specification would then define the taxonomic group targeted through polymerase chain reaction amplification, such as fish eDNA, invertebrate eDNA and bacterial eDNA. This terminology does also not require assumptions about the specific state of the DNA sampled (intracellular or extracellular). We hope that such terminology will help better define the scope of eDNA studies, especially for environmental managers, who use them as reference in routine biomonitoring and bioassessment.